Pregnant Women's Compliance Experience In Consuming Fe Tablets In Bukittinggi City In 2024 - Diana putri (International Journal of Public Health, 2025)
Iron deficiency is a common cause of anemia during pregnancy. The low consumption of Fe tablets is related to compliance with consumption. The purpose of this study was to determine the compliance of pregnant women taking iron tablets in the second trimester in Bukittinggi City. This was a qualitative study using a case study method. A purposive sampling technique was used, with the main informant being pregnant women in the second trimester in Baratan Village. Data were collected using interview techniques, observation, and documentation analysis and then validated using data triangulation, observer triangulation, theory triangulation, and method triangulation. The results of this study were analyzed based on data grouping. Testing data assumptions, alternative data explanations, and the results of the study were written. The compliance of pregnant women in taking Fe tablets shows the compliance of pregnant women in the second trimester in taking Fe tablets and how pregnant women know the benefits and impacts of not taking Fe tablets. Researchers know how long pregnant women take Fe tablets, and family support is a reinforcement for pregnant women if they forget when taking Fe tablets. Pregnant women who routinely have ANC will also receive Fe tablets from the midwife who checks for compliance with taking Fe is better when Fe tablets are also available. The opinion of researchers of primigravida pregnant women in the second trimester shows that the first, second, and third subjects are pregnant women in the second trimester who have experience taking Fe tablets. They reported the same complaints, namely nausea and vomiting after taking Fe tablets; even so, they remained obedient and routinely took Fe tablets every day, with and without being reminded by their families, they still routinely took Fe tablets. Some mothers understand the impact of not taking Fe tablets, namely, anemia and bleeding. During the interviews, all mothers said that they routinely checked their pregnancy every month with a midwife accompanied by their husbands.